Nanograting-Based Dynamic Structural Colors Using Heterogeneous Materials - Jingang Wang; Haibo Yu; Jianchen Zheng; Yuzhao Zhang; Hongji Guo; Ye Qiu; Xiaoduo Wang; Yongliang Yang; Lianqing Liu (Nano-Micro Letters)
Highlights A 2.5-dimensional dynamic structural color based on nanogratings of heterogeneous materials was proposed by interweaving a pH-responsive hydrogel with IP-L photoresist. The nanogrid structures exhibit brilliant tuneable structural color, high sensitivity, and ultrafast recovery speeds in response to pH. The 4D printing-based grayscale design approach was proposed for the patterned encoding and array printing of dynamic structural colors, promoting their application in patterned printing, information encryption, and microfluidic chip sensing.